Investigating the potential benefit of second biopsy of residual mass in pediatric mature B cell non-Hodgkin lymphoma. (17th February 2019) - Cai, Mengxin; Wang, Tianyi; Pan, Ci; Gao, Yijin; Zhou, Min; Hu, Wenting; Ye, Qidong; Tang, Jingyan
Abstract: Objectives: To assess the impact of second-look biopsy of residual mass during or after chemotherapy in pediatric mature B-cell NHL. Methods: Patients with mature B-cell non-Hodgkin lymphoma (NHL) who were suspicious of radiological residual mass at mid or end of treatment and subjected to second biopsy were treated at our center between January 2001 and December 2015. Their clinical characteristics, imaging findings, pathological changes, management, and prognosis were reviewed retrospectively. Results: A total of 31 children were included (13 boys and 18 girls, median age at diagnosis 6.1 years). The median time from diagnosis to second biopsy was 3.15 months (range 2.3–18 months). Biopsy confirmed the presence of viable tumor in eight patients. The specificity and positive predictive value of conventional imaging in detecting residual detectable by biopsy were at 9 and 28.6%, while sensitivity and negative predictive value of this approach were both 100%. Three of the histologic positive patients experienced progressive disease or relapse while the others achieved complete remission (CR) and 21 patients achieved long-time CR at median follow-up of 3.2 years. The median progression-free survival (PFS) time of all 31 was 28 months and 5-year PFS rate was 90.0%. Five-year PFS rate of negative-biopsy and positive-biopsy group were 100 and 62.5%, respectively ( p  = 0.002). Conclusion: Conventional imaging has very high sensitivity but very low specificity for the accurate determination of residual disease in pediatric NHL. Second-look biopsy is necessary to differentiate viable tumor from necrosis or fibrosis and is solid evidence-based foundation of subsequent treatment.